Developing Syllabus And Instructional Materials For Advanced Reading Course In English Education Department of Ganesha University of Education - ., LAURENSIUS PUTU VERDIKA; ., DR. LUH PUTU ARTINI, M.A.; ., PROF. DR. NI NYOMAN PADMADEWI, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
Membaca adalah bagian penting dalam bahasa Inggris and aktifitas pembelajaran dalam bahasa Inggris untuk pelajar asing. Sasaran dari membaca adalah membaca untuk hal umum, membaca untuk suatu informasi yang khusus, membaca untuk mendapatkan informasi yang detail dan membaca untuk kesenangan. Penelitian ini bertujuan untuk mengembangkan silabus dan materi pembelajaran untuk mata kuliah Advanced Reading Course pada semester 5 di Universitas Pendidikan Ganesha (Undiksha). Pengumpulan data mennggunakan model Sugiyono (2015): (1) rumusan masalah, (2) Pengumpulan data, (3) Desain Produk, (4) Validasi Desain, (5) Revisi Desain, (6) Prototype, (7) Field tests. Model terakhir (field test) tidak sepenuhnya dipergunakan karena keterbatasan waktu dan biaya. Data penelitian ini juga didukung oleh penelitian sebelumnya yang sudah berhasil memperoleh data melalui kuestioner, checklist, analisis dokumen, dan FGD. Subject dalam penelitian ini adalah para dosen pengampu mata kuliah Advanced Reading di jurusan pendidikan bahasa Inggris and objek penelitian in adalah silabus dan materi pembelajaran English Advanced Reading. Hasil dari penelitian ini menunjukkan bahwa (1)silabus terdahulu yang sudah diapplikasikan dalam proses pembelajaran Advanced Reading Course di Undiksha tidak sesuai dengan kebutuhan mahasiswa. Kemudian, melalui serangkaian penelitian, silabus sudah di revisi dengan mempergunakan teori strukur silabus oleh Johnson (2006). (2) Silabus yang telah direvisi menjadi kerangka utama untuk menghasilkan materi Advanced Reading yang lebih baik. Teori good material Tomlinson (1998) dipergunakan untuk memperkuat materi Advanced Reading. (3) Prototype ini adalah produk yang memilki kualitas berdasarkan bahwa kualitas dalam sebuah produk bias diukur melalui validitas, kegunaan, dan keefektifan produk tersebut. Sebagai penutup, peneliti berharap bahwa hasil penelitian ini bias bermanfaat untuk meningkatkan kemampuan berbahasa Inggris dan juga sebagai model bagi para dosen untuk mengembangkan materi Advanced Reading. Kata Kunci : Silabus, Materi Pembelajaran, Advanced Reading Course Reading is the key component of English and teaching activity for English for Foreign English students. The objectives of reading are to read for general, to read for specific information, to read for detailed information, and to read for pleasure. This study aimed to develop syllabus and Instructional materials for Advanced Reading course of fifth semester students in English Education Department Ganesha University of Education Singaraja. The data collection utilized Sugiyono (2015) model: (1) problems, (2) data collection, (3)product design, (4) design validation, (5) design revision, (6) Prototype, (7) conducting field tests. The last model (conducting field test) was not fully applied due to the fact that this study dealt with limitation of time and lack of financial support. The data were also supported by the preliminary research which could obtain data throughout questionnaire, checklist, document analysis, and focus group discussion (FGD). The subject of this study was the lectures who have taught Advanced Reading course in English Education Department and the object of this study were the syllabus of Advanced Reading course and Instructional material used for teaching Advanced Reading course. The result of the study pointed out that (1) the existing syllabus applied in Advanced Reading Course at Undiksha was not compatible and did not meet the students’ needs. Thus, throughout a series of research, the syllabus had been revised by utilizing the syllabus structure by Johnson (2006). (2) The revised syllabus had been the core structure in order to create better advanced reading materials. The theory of good materials (Tomlinson, 1998) was applied to strengthen the advanced reading materials. (3)This prototype was a qualified product due to the fact that the quality of the product can be measured by its validity, practicality, and effectiveness. As the final remark, the researcher hopes that the result of this study could be useful for building students’ language competence and performance, as well as can serve as a model for lecturer to develop their own advanced reading materials. keyword : Syllabus, Instructional Materials, Advanced Reading Course